2004
DOI: 10.1080/0887044042000193460
|View full text |Cite
|
Sign up to set email alerts
|

Physical recovery in Arthroscopic knee surgery: unique contributions of coping behaviors to clinical outcomes and stress reactivity

Abstract: Few studies have examined whether certain coping behaviors are associated with physical outcomes following surgery. This prospective, longitudinal study investigated the effect of active and avoidant coping behaviors on two physical outcomes over time, pain and knee function, in a group of patients experiencing knee arthroscopic surgery (n ¼ 81). Structured interviews and physician clinical assessments were conducted preoperatively and at 3 and 24 weeks postoperatively. Coping behavior was assessed during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…A summary score ranging from 0 to 100 points is generated, with a higher score reflecting better knee function. The Tegner-Lysholm rating scale is the most widely used patient-reported outcome instrument in orthopaedic research [6,8,15,17,22] and is acceptable, reliable, and valid [10]. Knee function was assessed preoperatively to provide a baseline knee function score.…”
Section: Methodsmentioning
confidence: 99%
“…A summary score ranging from 0 to 100 points is generated, with a higher score reflecting better knee function. The Tegner-Lysholm rating scale is the most widely used patient-reported outcome instrument in orthopaedic research [6,8,15,17,22] and is acceptable, reliable, and valid [10]. Knee function was assessed preoperatively to provide a baseline knee function score.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to the studies that had conducted their own exploratory factor analyses, those that based their factor structure on previous research tended to have smaller samples sizes. Of the 34 studies listed in Table 3, 14 studies had a sample size of less than 100 [77][78][79][80][81][82][83][84][85][86][87][88][89][90]. Some of the studies had more than 300 participants [91][92][93], where a factor analysis would have been supported by a sufficiently large sample size.…”
Section: Studies That Did Not Conduct Their Own Exploratory Factor Anmentioning
confidence: 99%
“…It is the most widely used patient-reported knee function outcome instrument in orthopaedic research [29][30][31][32] and has demonstrated reliability and validity 33 . Items are differentially weighted on the basis of clinical criteria, and a summary score ranging from 0 to 100 points is obtained, with a higher score reflecting better knee functioning.…”
Section: Primary Outcome Measurementioning
confidence: 99%